Facile gamma radiolytic synthesis of synergistic Co3O4-rGO nanocomposite: direct use in photocatalytic water splitting - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dash, S.; Tyagi, A. K. (Materials Research Express, 2014)
Nanostructured Co3O4 was synthesized through a gamma (gamma)-radiolysis technique using alcoholic (iso-propanol) salt solutions of cobalt ions with and without suspended graphene oxide (GO) nanoparticles, respectively. Formation of Co3O4 accompanied with GO reduction takes place simultaneously (in situ) upon.-ray exposure carried out at a rate of 5.1 KGy h(-1). Reduction of GO and formation of Co3O4 were confirmed by XRD, Raman and UV-vis spectroscopy. XRD and HRTEM results supports the embedding of nano-crystalline Co3O4 in an amorphous matrix. Relatively larger crystallites of cobalt oxide obtained in the presence of rGO proved to be a decisive supporting material for the directional growth of Co3O4. Electrochemical characterization established the fact that rGO is indeed considered as a proficient medium for electrochemical electron transfer process. Photo-assisted H-2 generation studies using Co3O4 and Co3O4-rGO nano-composite yielded 3 and 30 mu mol h(-1) g(-1) of hydrogen (H-2) generation, respectively, supports the action of rGO as an electron trap.
Keywords: nano cobalt oxide; photocatalytic hydrogen production; Reduced graphene oxide